Music Perception of Cochlear Implant Recipients and Implications for Counseling and (Re)habilitation. - Gfeller, Kate (Perspectives on Hearing & Hearing Disorders: Research & Diagnostics, 2012)
Next to improved spoken communication, satisfactory music perception and enjoyment is the second most common aspiration of cochlear implant (CI) recipients (Gfeller et al., 2000). This article provides an overview of research regarding music perception of CI recipients. The author characterizes perceptual acuity and appraisal (sound quality) for structural attributes of music (pitch, timbre, rhythm) as influenced by technical characteristics of the device, characteristics of the CI user, and training. These research findings will be related to practical aspects of music enjoyment in everyday life, speech in conjunction with music, and general CI benefit.